THE ROLE OF STUDENT VOLUNTEERING ACTIVITIES IN THE DEVELOPMENT OF ACADEMIC COMPETENCIES OF STUDENTS INVOLVED IN INCLUSIVE AND HOME EDUCATION - Dilfuza Azamkhulovna Pulatova (Modern American Journals, 2025)
This article analyzes the role of volunteer students in the development of academic and social competencies of students with special needs within the framework of inclusive and home education. The article explores the historical roots of the volunteer movement, global experience, the activities of the Association of Volunteers of Uzbekistan, and initiatives such as the "Bir safda" social movement and the "Pedagogik desantura" club of the Special Pedagogical Department of Chirchik State Pedagogical University (CHDPU). The study examines the influence of student volunteers on children with special needs in the educational process and their influence on socio-academic skills. The results show the importance of volunteer activities in improving the quality of education and opportunities for future development.
Keywords: Volunteer students, inclusive education, home-based learning, academic competencies, social adaptation, special educational needs, Uzbekistan Volunteer Association, CHDPU initiatives